FEASIBILITY STUDY ON ESTABLISHING THE INTERNATIONAL CENTRE FOR SOCIAL WELFARE AND SOCIAL POLICY - Ćukalović, Vukica (Ревија за социјална политика/Journal of Social Policy, 2015)
The feasibility study is a planned activity, caused and shaped bysocial motives reflecting through the specific features of the constantprocess (from one system of values into another system of values). Theaccompanying experience imposes a need of efficient implementation andproper practice of social work in resolving of all transitional effects. Thisimplies knowledge in action or the ability to use knowledge, personalcapacity and resources. The objective is defined by initiating the processof changes as the ability of a social worker for permanent upgrading of theprofessional role, authenticity, dignity and based on the values and skillsof the social work.